2014
DOI: 10.1128/iai.01435-13
|View full text |Cite
|
Sign up to set email alerts
|

Escherichia coli Pathotypes Occupy Distinct Niches in the Mouse Intestine

Abstract: bSince the first step of the infection process is colonization of the host, it is important to understand how Escherichia coli pathogens successfully colonize the intestine. We previously showed that enterohemorrhagic O157:H7 strain E. coli EDL933 colonizes a niche in the streptomycin-treated mouse intestine that is distinct from that of human commensal strains, which explains how E. coli EDL933 overcomes colonization resistance imparted by some, but not all, commensal E. coli strains. Here we sought to determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 33 publications
(55 reference statements)
2
35
0
Order By: Relevance
“…coli within the gut comes from studies showing that different E. coli strains can simultaneously colonize the mouse intestinal tract if they can utilize distinct nutrients (42, 43). The extent to which two E.…”
Section: Discussionmentioning
confidence: 99%
“…coli within the gut comes from studies showing that different E. coli strains can simultaneously colonize the mouse intestinal tract if they can utilize distinct nutrients (42, 43). The extent to which two E.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, colonization by the enterohemorrhagic Escherichia coli strain EDL933 was blocked by a complementary mixture of commensal strains that effectively occupy the various intestinal niches that serve as colonization sites for EDL933 (41). Subsequent work revealed that other E. coli pathotypes target other intestinal sites for colonization (42), indicating that further investigation of the link between strain diversity and niche specificity is necessary to develop broad-spectrum probiotics. Interestingly, in some cases, strain diversity of pathogens within a mixed infection may augment the corresponding disease.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, when the ability of E. coli EDL933 to colonize mice that were pre-colonized with E. coli HS and E. coli Nissle 1917 was tested, which the data in Table 2 indicate should be equally effective without E. coli MG1655 present, E. coli EDL933, was indeed eliminated 5 days following association (35). However, the same 2 commensal E. coli strains could not prevent colonization of E. coli CFT073, a uropathogenic strain, and E. coli E2348/69, an enteropathogenic strain (95). Therefore, it is unlikely that any particular commensal strain(s) of E. coli will be generally effective as a probiotic to prevent colonization by enteric pathogens.…”
Section: Competition For Nutrients In the Intestinementioning
confidence: 99%